Halal Tourism Industry for The Micro Economy in Gorontalo: Potential, Opportunity and Challenges - Dian Adi Perdana; Moh Hidayat Tomayahu; Titin S. Kaaba (Jurnal Penelitian, 2022)
This research is to analyze and examine the prospects, potentials and obstacles to the development of halal tourism to build a micro-economy in Gorontalo. This research is a field research, with qualitative analysis, which is descriptive. The data sources in this study are primary data and secondary data. Techniques for taking the subject of this research are interviews, observation and documentation. The data obtained, processed so as to obtain the final conclusion. The results of this study are tourism marketing strategies throughout Gorontalo Province have not been running well and in accordance with the wishes of tourist visitors because there are still many obstacles that need to be resolved. SWOT analysis is diversification, meaning that tourism in Gorontalo Province Cultural tourism and nature tourism are in prime condition but there are threats that need to be anticipated. The strength and threat factors are greater than the weaknesses and opportunities and other factors. Therefore, it is a profitable position and must be watched out for, the manager has good strength and there are threats from external or competitors for halal tourism in other provinces in Indonesia, so that the manager can utilize the internal strengths of the tours they have to the maximum and management parties also need to implement strategies that can minimize external threats, by making policies, forming an implementing team and a supervisory team to support tourism in Gorontalo Province to become visitor-friendly halal tourism.